2020
DOI: 10.1021/acs.jpcc.0c02146
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Driven Solid State Phase Transformation of Co3O4 to CoO Nanoparticles

Abstract: The phase transition of Co3O4 into CoO is demonstrated by the impact of shock waves, and the mechanism is studied and reported. The required quantity of Co3O4 nanoparticle (NPs) is synthesized by coprecipitation method. 2.0 MPa transient pressure shock wave is utilized to understand the shock wave induced phase transition in Co3O4 NPs. XRD and Raman studies reveal that the phase transition occurs at 150 shocks in loaded condition. The obtained values of optical band gap energy show that there are changes in ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 39 publications
(62 reference statements)
0
73
0
Order By: Relevance
“…Here, the results of a few technologically important nanocrystalline materials are presented based on the observed shock wave-induced structural phase transitions and lattice deformations which give a clear idea on the substantiation of the present experimental results. Anatase TiO 2 NPs are found to be crystallographically phase transformed to rutile-TiO 2 at 90 shock pulses loaded conditions [14], while Co 3 O 4 NPs are observed to be transformed to CoO NPs at 150 shocked conditions [20]. On the other hand, in the case of Fe 2 O 3 NPs, the X-ray diffraction peak intensity is found to have suffered with a significant reduction with respect to the number of shock pulses and grain size is also observed with a significant reduction due to the existence of the lattice deformations and breaking of internal grain boundaries [15].…”
Section: Structural Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Here, the results of a few technologically important nanocrystalline materials are presented based on the observed shock wave-induced structural phase transitions and lattice deformations which give a clear idea on the substantiation of the present experimental results. Anatase TiO 2 NPs are found to be crystallographically phase transformed to rutile-TiO 2 at 90 shock pulses loaded conditions [14], while Co 3 O 4 NPs are observed to be transformed to CoO NPs at 150 shocked conditions [20]. On the other hand, in the case of Fe 2 O 3 NPs, the X-ray diffraction peak intensity is found to have suffered with a significant reduction with respect to the number of shock pulses and grain size is also observed with a significant reduction due to the existence of the lattice deformations and breaking of internal grain boundaries [15].…”
Section: Structural Analysismentioning
confidence: 97%
“…In recent years, many research groups have been working relentlessly to find out high shock wave-resistant materials for space applications which includes our research group as well [5,6]. So far, shock wave-resistant properties of a few of metal oxides and divalent ferrite nanocrystalline materials such as TiO 2 [14], a-Fe 2 O 3 [15], ZrO 2 [16], ZnO [17], a-MnO 2 [18], NiO [19], Co 3 O 4 [20], CuO [21], AgO [22], CeO 2 [23], ZnFe 2 O 4 [24], NiFe 2 O 4 [25], and MnFe 2 O 4 [26] have been reported. Based on the available literature survey, it has been demonstrated that shock wave-induced phase transformation from anatase to rutile of TiO 2 NPs [14] and cubic ZrO 2 to monoclinic-ZrO 2 can be achieved using piston-driven shock tube [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After synthesizing the anatase and rutile TiO 2 , dynamic shock waves have been loaded on the samples for which the required shock waves have been generated by a shock tube (Semi-automated Reddy tube). The details of the working of the shock tube and generation of shock waves have been discussed in our earlier publications [18,29] and the details of the shock wave loading procedure are presented in the supplementary section. In the present case, shock waves of Mach number 2.2 that has the transient pressure and temperature of 2.0 MPa and 864 K, respectively are utilized.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…As a consequence of this, shock wave induced research on crystalline as well as non crystalline materials has gradually gained momentum in recent years [7][8][9][10]. Particularly in nano-crystalline materials of metal oxides, there have been impressive results documented by several research groups including our research group in the last couple of years [11][12][13][14][15][16][17][18][19][20][21][22][23]. So far, crystallographic phase stabilities of several technologically important metal oxide NPs and their shock resistant profiles have been reported which are such as ZrO 2 (Fm-3 m) [11], ZnO (P6 3 mc) [12] α-MnO 2 (I4/m) [13], TiO 2 NPs (I4 1 /amd) [14][15][16][17], Co 3 O 4 (Fd-3 m) [18], NiO (Fm-3 m) [19], CeO 2 (Fm-3 m) [20] CuO (Bmm2) [21] α-Fe 2 O 3 (R-3c) [22], AgO (P2 1 /c) [23].…”
Section: Introductionmentioning
confidence: 99%